(untitled) (Bangladesh Journal of Medical Microbiology, 2016)
A total of 115 women were investigated along with 50 controls in order to find out association of Mycoplasma hominis in Bacterial Vaginosis (BV) cases. Vaginal swabs were collected from the cases enrolled from three tertiary- level Hospitals of Dhaka City during December, 1993 to December, 1994. Specimens were cultured on appropriate media and M. hominis was isolated from 28 (24.3%) specimens collected from patients and 3 (6%) from healthy controls. The difference of isolation rate was statistically significant (p<0.05) between cases and the controls. In addition to M. hominis, Gardnerella vaginalis was present in 35 (30.4%), Candida spp. in 26 (22.6%), Trichomonas vaginilis in 10 (8.7%) and other aerobic bacteria in 11 (9.5%) cases. Bangladesh J Med Microbiol 2008; 02 (01): 18-21 DOI: http://dx.doi.org/10.3329/bjmm.v2i1.21783